On the Oxypoda species of Turkey and adjacent regions. II. Three new species, additional records, and a checklist (Coleoptera: Staphylinidae, Aleocharinae) - Assing, Volker (Zootaxa, 2007)
Three species of Oxypoda Mannerheim from Turkey are described and illustrated: O. (Podoxya) pontica sp. n. (Rize), O. (Bessopora) aydinica sp. n. (Aydın), and O. (Mycetodrepa) obscuricollis sp. n. (Mersin). A new combination and a new synonymy are established: Oxypoda (Thliboptera) scheerpeltziana (Fagel, 1968), comb. n. (ex Aleochara) = Oxypoda micantoides Assing, 2006, syn. n. Additional records of previously described species are reported from Turkey (22 species), Lebanon (1 species), and Israel (1 species), among them the first Turkish records of O. brevicornis (Stephens), O. lesbia Assing, and O. recondita Kraatz, as well as the first record of O. ignorata Zerche from Lebanon. The distributions of 10 species are mapped. A checklist of all Oxypoda species reported from Turkey is compiled.